Peripheral vision tests in sports: Training effects and reliability of peripheral perception tests - Schumacher, N.; Schmidt, M.; Reer, R.; Braumann, K.-M. (International Journal of Environmental Research and Public Health, 2019)
Various studies suggest the importance of peripheral vision (PV) in sports. Computer-based test systems provide objective methods to measure PV. Nevertheless, the reliability and training effects are not clarified in detail. The purpose of this investigation was to present a short narrative non-systematic review on computer-based PV tests and to determine the reliability and the training effects of peripheral perception sub-test (PP) of the Vienna test system (VTS) in a test-retest design. N = 21 male athletes aged between 20 and 30 years (M = 26.15; SD = 3.1) were included. The main outcome parameters were peripheral reaction (PR), PR left (PRL), PR right (PRR), field of vision (FOV), visual angle left (VAL), and visual angle right (VAR). Reliability was assessed using intraclass correlation coefficient (ICC) and Bland-Altman plots. Training effects were determined by students t-test. Good reliability was observed in PR, PRL, and PRR. Moderate reliability was found in FOV, VAL, and VAR. Significant improvements between T0 and T1 were found in PRL with a mean difference of 0.04 s (95% CI [0.00-0.07]) and in PR with a mean difference of 0.02 s (95% CI [0.00-0.05]). For PRR, FOV, VAL, VAR, no significant differences were detected. These results indicate that PP can be applied to asses PV abilities in sports. Future research is needed to clarify the influence of test repetitions on visuomotor learning in PP. Moreover, PV tests should be cross-validated with sport-specific measurements (e.g., on-field and/or `virtual reality` approaches).